МИНЕРАЛОГИЯ И ТИПОМОРФИЗМ ЗОЛОТА КАЙНОЗОЙСКИХ РОССЫПЕЙ СЕВЕРА УРАЛА И ТИМАНА - Майорова Т.П. (My University, 1996)
Enormously high contents of Hg, Си and Pd impurities in placer gold of the Northern Urals are noted as its compositional peculiarities. Geochemical types of placer gold are established, with the regularities of their localization within the region shown. Typomorphic peculiarities of placer gold are identified, which indicate the distance of gold transfer from primary sources, nature of gold-bearing fluids, formational affiliation of primary endogenic ore occurrences, degree of hypergenic alteration.
Keywords: Кайнозойская; Кайнозой